The Effect of Advertising on the Sales of Small Enterprises in Uganda - Veronica Kabajungu (Uganda Christian University, 2023)
The purpose of the study sought to examine the relationship between advertising and the sales in Mukono Municipality. The study was guided by research specific objectives which included; to examine the relationship between brand awareness and sales of enterprises in Mukono Municipality, to determine examine the relationship between humor and advertising on sales of Mukono Municipality, to examine the relationship between brand trust in the context study. The study was a cross sectional survey that used questionnaires and interview guide to collect data from a sample of 61 respondents. Quantitative data was analyzed using SPSS software application and percentage tables were derived using descriptive techniques analysis. The findings revealed that there was appositive link between advertising and the volume of sales in small enterprises of Mukono Municipality. For instance, the findings revealed that advertising to a larger extent has contributed to a largest percentage of the total sales in the small enterprises. Therefore, in order to yield and keep up the full benefits of advertising, the small enterprise, should properly channel the resources so as not to be misused, proper advertising should be used to alert and inform the public about the product so as to maintain its sales volume.
This is a dissertation.